Total Sleep Deprivation Does Not Significantly Degrade Semantic Encoding - Honn, KA (Chronobiol Int, 2018)
Sleep deprivation impairs performance on cognitive tasks, but it is unclear which cognitive processes it degrades. We administered a semantic matching task with variable stimulus onset asynchrony and both speeded and self-paced trial blocks. The task was administered at baseline and 24 hours later after 30.8 hours of total sleep deprivation or matching well-rested control. After sleep deprivation, the 20% slowest response times were significantly increased. However, the semantic encoding time component of the response times remained at baseline level. Thus, the performance impairment induced by sleep deprivation on this task occurred in cognitive processes downstream of semantic encoding.